2019
DOI: 10.1523/eneuro.0424-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

The Rat Medial Prefrontal Cortex Exhibits Flexible Neural Activity States during the Performance of an Odor Span Task

Abstract: Medial prefrontal cortex (mPFC) activity is fundamental for working memory (WM), attention, and behavioral inhibition; however, a comprehensive understanding of the neural computations underlying these processes is still forthcoming. Toward this goal, neural recordings were obtained from the mPFC of awake, behaving rats performing an odor span task of WM capacity. Neural populations were observed to encode distinct task epochs and the transitions between epochs were accompanied by abrupt shifts in neural activ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 48 publications
0
19
2
Order By: Relevance
“…Previous work in our laboratory has shown that performance of the OST relies on the mPFC and dorsomedial striatum (Davies et al 2017a,b). We have also recently found that delay period spiking of mPFC neurons is predictive of WM performance in the OST (De Falco et al 2019), showing an involvement of delay period activity in the mPFC. However, we found in a separate experiment that performance of the OST is independent of the parietal cortex (Scott et al 2018), in contrast to ample previous research showing an important role for the PC in WM.…”
mentioning
confidence: 68%
“…Previous work in our laboratory has shown that performance of the OST relies on the mPFC and dorsomedial striatum (Davies et al 2017a,b). We have also recently found that delay period spiking of mPFC neurons is predictive of WM performance in the OST (De Falco et al 2019), showing an involvement of delay period activity in the mPFC. However, we found in a separate experiment that performance of the OST is independent of the parietal cortex (Scott et al 2018), in contrast to ample previous research showing an important role for the PC in WM.…”
mentioning
confidence: 68%
“…7a-f). Furthermore, we analyzed neuron waveforms to differentiate excitatory and inhibitory neurons 40, 41 (Supplemental Fig. 11).…”
Section: Resultsmentioning
confidence: 99%
“…The waveform was rescaled from -1 (maximum hyperpolarization amplitude) to 1 (maximum post-action potential depolarization peak). Similar to previously used methods 40, 41 , we classified the neurons using time delays associated the waveform depolarization. We used the time to 50% depolarization and the time to 95% depolarization as the time delays to characterize the speed of the depolarization.…”
Section: Methodsmentioning
confidence: 99%
“…Delayed non-match to sample (DNMTS) paradigms hinge on such memoryguided decisions and are subserved by interactions between executive and mnemonic hub regions including the prefrontal cortex (PFC) and hippocampus 2,3 . PFC principal neuron spike rates during delayed response tasks encode diverse features of sample identity and task rules in both non-human primates [4][5][6][7][8] and rodents [9][10][11][12][13][14][15] , with sustained PFC principal neuron firing offering an intuitive neural correlate of working memory maintenance during task delay phases 16,17,[26][27][28][29][30][31][32][18][19][20][21][22][23][24][25] . However, as analyses have extended from individual neurons to simultaneously recorded cortical populations, other informative features of PFC ensemble dynamics have emerged [33][34][35] .…”
Section: Introductionmentioning
confidence: 99%